STABILIZED DISCRETIZATIONS AND ROBUST PRECONDITIONERS FOR THE POROELASTIC EQUATIONS - Ohm, Peter. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Mathematics.; Advisors: James Adler, and Xiaozhe Hu.; Committee: Grant Garven, Johannes Kraus, and Ludmil Zikatanov.; Keywords: Applied mathematics, and Mathematics.